2014
DOI: 10.1186/1758-5996-6-115
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between reduction of superior interventricular groove epicardial fat thickness and improvement of insulin resistance after weight loss in obese men

Abstract: BackgroundIt has been recognized that reduction of abdominal visceral fat and subcutaneous fat are associated with improvement in insulin-resistance (IR) after weight loss. However, few studies have investigated the correlation of reduction in epicardial adipose tissue (EAT) with improvement of IR index after weight loss in obese non-diabetic men with metabolic syndrome (MetS).Methods and resultsWe prospectively enrolled 32 non-diabetic men with MetS for a 3-month weight reduction program mainly by diet contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Weight loss by diet control or exercise could result in significant reduction of EAT in interventricular groove, which was correlated with improved insulin resistance and insulin sensitivity indexes . Diet control and bariatric surgery induced weight loss in obese individuals was associated with EAT reduction, while no such effect was observed after exercise .…”
Section: Potential Therapiesmentioning
confidence: 92%
“…Weight loss by diet control or exercise could result in significant reduction of EAT in interventricular groove, which was correlated with improved insulin resistance and insulin sensitivity indexes . Diet control and bariatric surgery induced weight loss in obese individuals was associated with EAT reduction, while no such effect was observed after exercise .…”
Section: Potential Therapiesmentioning
confidence: 92%
“…[15][16][17] Investigators have reported that epicardial fat is associated with endothelial dysfunction, 18 insulin resistance, 19 and inflammatory markers. 20 According to further study results, EFT is related to subclinical target-organ damage such as aortic stiffness, 21 carotid intima-media thickness, and carotid plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial fat thickness is associated with insulin resistance, which might be responsible for impaired arterial function. 19 Increased expression of secretory type II phospholipase A 2 in epicardial adipose tissue might be responsible for endothelial dysfunction and increased arterial stiffness. 27 Kim and colleagues, 21 who consecutively enrolled 655 subjects who underwent echocardiography and ankle-brachial pulse-wave velocity measurement, found that individuals with increased velocity and EFT had unfavorable metabolic and lipid profiles, and that EFT was significantly associated with ankle-brachial pulse-wave velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Parts of the results have been published previously. [ 16 19 ] In brief, the study enrollment criteria included central obesity, which was defined as waist circumference ≥ 90 cm, in addition to at least 2 other ATP-III MetS criteria. [ 20 ] Patients with DM requiring oral anti-diabetic agents or insulin shots were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%